Understanding cultural differences in ethnic employees' work values: a literature review - Daria Gom; Mary Monica Jiony; Geoffrey Harvey Tanakinjal; Ruth S. Siganul (Scientific & Academic Publishing, 2015)
Work values are very much influenced by employees’ cultural values and traits. For this study, a qualitative approach on past research and literature was employed. By exploring recent cross cultural research in Malaysia, this paper provides a critical review on the cultural differences of ethnic groups in Malaysia, specifically among the Sabah ethnics employees working in Sabah, Malaysian Borneo. Malaysia is a multicultural country and each ethnic group may not share the same cultural values due to its distinct separate identities and cultures. This study also discusses the findings of researchers on the differences of Malaysian and western work values and their underlying assumptions. In addition, this review hopes to enhance further knowledge and understanding on Sabah Borneo ethnic cultural values and behavior in the workplace for effective management of ethnic diverse employees in pursuit of organizational success.